The Existence of Customary Law in Renewing the National Legal System - Femmithasari, Nadia Indah (Universitas Negeri Semarang, 2023)
The renewal of national law in Indonesia is an effort to modernize the law in creating positive law that is in tune with the times. In this reform effort, customary law is considered as a reflection of ancestral values ​​that are very in line with the basic foundations, sources, and materials of national law so that it will be used as a benchmark in the process of reforming the national legal system. This manuscript is the development of the sub-themes, namely indigenous peoples and national law. The focus of the problem that will be raised is how customary law that grows in the community can become the main basis in efforts to reform the national legal system in Indonesia. It is important to recognize the values ​​that live in society as customary law in the renewal of the national legal system which is a demand and need to fulfill the national ideals of the Indonesian nation.